Improvement through Selection of Plus Trees in Khasipine (pinus Kesiya) - Singh, Ombir; Mahanta, N. (Indian Forester, 2013)
33 plus trees of Pinus kesiya were selected in an extensive survey conducted in the state of Meghalaya using point grade method of selection. Initially candidate plus trees (CPT's) along with five check trees were selected and analyzed to plus trees. During selection, phenotypic characters like stem, bole, and branching form were given more emphasis to ensure better production of timber. The plus trees over check trees could be improved by 14.75, 15.74 and 14.23% for height, girth at breast height (GBH) and crown bole height (CBH), respectively. Maximum improvement of 138.61, 105, 99, and 51.53% was recorded for crown, straightness, roundness, and pruning ability, respectively, which might play an important role in accepting this species in plantation programmes. The improvement achieved through selection may serve as an indicator for possible genetic gain after field-testing through progeny trials in the species.